2017
DOI: 10.2147/rru.s143865
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor assessment in high-risk, bacillus Calmette–Guérin-treated, non-muscle-invasive bladder cancer

Abstract: ObjectiveTo assess the risk factors associated with recurrence, progression and survival in high-risk non-muscle-invasive bladder cancer (NMIBC) patients treated with bacillus Calmette–Guérin (BCG) and validate the European Organization for Research and Treatment of Cancer (EORTC) and Spanish Urological Club for Oncological Treatment (CUETO) scores.Patients and methodsWe retrospectively analyzed all BCG-treated NMIBC patients from 1998 to 2012. Multiple variables were tested as risk factors for recurrence-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Evaluation of smoking habits was based on hospital records. In our present study, the percentage of never smokers was similar to patients treated with BCG instillation described elsewhere . The reported total number of eight BCG instillations does not take into account whether the patients completed their first series of six BCG instillations, had maintenance therapy or a second series of instillations.…”
Section: Discussionsupporting
confidence: 75%
“…Evaluation of smoking habits was based on hospital records. In our present study, the percentage of never smokers was similar to patients treated with BCG instillation described elsewhere . The reported total number of eight BCG instillations does not take into account whether the patients completed their first series of six BCG instillations, had maintenance therapy or a second series of instillations.…”
Section: Discussionsupporting
confidence: 75%
“…Most MIBCs arise from carcinoma in situ (CIS), a flat, high-grade, superficial urothelial lesion that is characterized by TP53 mutations and accounts for approximately 10% of all diagnosed bladder tumors [ 3 ]. CIS is considered to be an obligate precancerous lesion, while concomitant CIS is associated with a markedly worse prognosis in patients with bladder cancer, a fact that is mirrored in multiple clinical risk scores (Spanish Urological Club for Oncological Treatment (CUETO), European Organization for Research and Treatment of Cancer (EORTC)) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 43 of these studies (70%), BCG was used in all patients (100% treatment rate). 16,17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][40][41][42][43][44]46,49,51,54,56,57,[61][62][63]65,68,69,[72][73][74][75][76] BCG therapy was an inclusion criterion for some of these studies, which contributed to this high rate. In the remaining 18 studies (30%), the reported use of BCG instillations in HR-NMIBC patients ranged from 3% to 86%.- 18,20,39,45,47,48,50,…”
Section: Treatment Patternsmentioning
confidence: 99%
“…In the remaining 18 studies (30%), the reported use of BCG instillations in HR-NMIBC patients ranged from 3% to 86%.- 18,20,39,45,47,48,50,52,53,55,[58][59][60]64,66,67,70,71 Thirty-five studies reported on the use of BCG induction therapy specifically, 16,17,20-22,24-28,31,33-37,40,42,45,47,49,51,52, ClinicoEconomics and Outcomes Research 2022:14 https://doi.org/10.2147/CEOR.S341896 DovePress 37 54,56,57,59,61,63,65,68,74,75,77,78 of which 27 (77%) reported the use of BCG induction in all patients (100%). 16,17,21,22,[24][25][26][27][28]31,[33][34][35][36][37]40,42,49,…”
Section: Treatment Patternsmentioning
confidence: 99%
See 1 more Smart Citation